Undergraduate tutoring: is it possible to succeed in a full-time course? (Research, Society and Development, 2023)
Academic monitoring provides a dialogical channel between professors and students, capable of favoring all processes involved in professional training in health. The present study is an experience report whose objective is to describe the performance of the Monitoring of Integral Health Care (AIS) within the scope of the Support Program for the Qualification of Undergraduate Teaching (PGRAD), Monitoring Subprogram (PGRAD-MONITORIA), from September to December 2019 in the medical course at the Federal University of Pará. The methodology involved four monitors, one with a scholarship and three volunteers, who assisted in teaching-learning remotely and in person. The monitors worked on formatting the teaching plan and collecting data from the students' evaluation. Students were divided into groups and allocated to Family Health Strategies (ESF) for practices and consolidation of theoretical knowledge. The results indicated that the teaching methodology by project benefited the students' learning, and the monitoring allowed to improve the teaching-learning process. In addition, two projects were transformed into extension projects, expanding their impact on the community. It is concluded that monitoring is a valuable educational strategy, allowing monitors to experience self-regulated learning and improving the training of future health professionals, who acquire new skills and competencies through this practice. Monitoring also brings students closer to teaching and expands postgraduate possibilities through the tripod of teaching, research and extension.